Inflation dynamics and international linkages: a model of the United States, the euro area and Japan - Günter Coenen; Volker Wieland (European Central Bank (ECB), 2002)
In this paper we estimate a small macroeconometric model of the United States, the euro area and Japan with rational expectations and nominal rigidities due to staggered contracts. Comparing three popular contracting specifications we find that euro area and Japanese inflation dynamics are best explained by Taylor-style contracts, while Buiter-Jewitt/Fuhrer-Moore contracts perform somewhat better in fitting U.S. inflation dynamics. We are unable to fit Calvo-style contracts to inflation dynamics in any of the three economies without allowing either for ad-hoc persistence in unobservables or a significant backward-looking element. The completed model matches inflation and output dynamics in the United States, the euro area and Japan quite well. We then use it to evaluate the role of the exchange rate for monetary policy. Preliminary results, which are similar across the three economies, indicate little gain from a direct policy response to the exchange rate.
Keywords: E31; E52; E58; E61; 330